Neoadjuvant therapy does not affect lymph node ratio in rectal cancer. Issue 5 (October 2016) - Chang, K.H.; Kelly, N.P.; Duff, G.P.; Condon, E.T.; Waldron, D.; Coffey, J.C.
Abstract: Aims: Recently, lymph-node ratio (LNR) has emerged as a prognostic tool in staging rectal cancer. Studies to date have demonstrated threshold values above and below which survival is differentially altered. Neoadjuvant therapy significantly reduces the number of lymph node retrieved. The aim of the present study was to determine the effect of neoadjuvant therapy on LNR and its prognostic properties. Methods: Consecutive patients who underwent curative rectal cancer resections in a single institution from 2007 to 2010 were reviewed. LNR was stratified into five subgroups of 0, 0.01–0.17, 0.18–0.41, 0.42–0.69 and 0.7–1.0 based on a previous study. The effect of neoadjuvant therapy on lymph node retrieval, LNR, locoregional (LR) and systemic recurrence (SR), disease-free (DFS) and overall survival (OS) was compared between patients who did (Neoadjuvant) and did not (Surgery Alone) receive neoadjuvant therapy. Results: Neoadjuvant and Surgery Alone groups were comparable in gender, age and tumour stage. The number of lymph nodes retrieved were significantly lower in the Neoadjuvant group ( p < 0.01). However, LNR remained similar in both groups ( p = 0.36). There was no statistical difference in the DFS and OS between the Neoadjuvant and Surgery Alone groups at the various LNR cut off values in patients with AJCC Stage 3 tumours. Conclusions: LNR ratio remains unaltered despite reduced lymph node retrieval after neoadjuvant therapy in rectal cancer. LNR may therefore be a more reliable prognostic indicator in this subgroup of patients.